Improved method for preparing a self-cleaning functional ceramic surface nanocoating
Patent Information
- Application Number
- CN202611066236.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-09-18
AI Technical Summary
[0003]现有传统制备工艺在长期工业化应用中暴露出一体化难以解决的综合缺陷,成为功能性自清洁陶瓷批量投产的核心阻碍
[0021] 1. This invention adds a low-temperature plasma activation modification process after the ceramic substrate cleaning process. Unlike traditional processes that only use water rinsing for degreasing, plasma bombardment simultaneously improves the micro-roughness of the ceramic glaze and introduces a large number of hydroxyl active groups onto the ceramic surface, enhancing the interfacial chemical bond strength between the titanium-silicon composite nano-sol and the ceramic substrate. After treatment with this improved process, the coating-substrate bond strength is enhanced. Even after long-term immersion in acidic or alkaline kitchen and bathroom wastewater and repeated wiping and friction, the coating shows no peeling, complete detachment, or localized damage, extending the lifespan of the self-cleaning ceramic coating, reducing the return rate of end products, and adapting to the long-term humid conditions of kitchens and bathrooms. This addresses the core defect of insufficient adhesion in existing products at the substrate interface level.
Smart Images

Figure CN122771806A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nano-coating preparation technology, and in particular to an improved method for preparing a self-cleaning functional ceramic surface nano-coating. Background Technology
[0002] Ceramic materials, with their high hardness, resistance to acid and alkali corrosion, high temperature resistance, and excellent glaze decorative texture, are widely used in kitchen and bathroom fixtures, building wall and floor tiles, daily-use craft ceramics, and industrial special wear-resistant ceramics. To address the industry pain points of easily adhering to oil stains, limescale, limescale, and pigment stains on ceramic glazes, and the time-consuming, labor-intensive, and costly manual cleaning, the mainstream industry approach is to use the sol-gel method to prepare a titanium dioxide-based nano-self-cleaning coating on the ceramic surface. This coating relies on the photocatalytic oxidation and decomposition of organic contaminants on the surface by titanium dioxide, while hydrophobic modification reduces water stain adhesion.
[0003] Existing traditional preparation processes have revealed comprehensive defects in long-term industrial applications, which are difficult to resolve in an integrated manner, becoming the core obstacle to the mass production of functional self-cleaning ceramics. Traditional sol preparation only uses tetrabutyl titanate as a titanium source precursor for hydrolysis, without simultaneous compounding and synergistic modification with tetraethyl orthosilicate and siloxane. After the coating is cured, there are many internal pores and the overall density is low. The pretreatment of the ceramic substrate only involves simple rinsing with water to remove oil, lacking a low-temperature plasma surface activation process. The ceramic glaze has extremely strong chemical inertness, and the interfacial bonding strength between the nano-coating and the ceramic substrate is insufficient. After long-term water washing and friction use, the product is prone to failure problems such as peeling, detachment of entire pieces, and surface scratches and damage. Therefore, in order to solve these problems, an improved method for preparing nano-coatings on the surface of self-cleaning functional ceramics is proposed. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing an improved method for preparing a self-cleaning functional ceramic surface nano-coating.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] An improved method for preparing a self-cleaning functional ceramic surface nano-coating includes the following steps:
[0007] S1 ceramic substrate pretreatment, cleaning and drying, followed by low-temperature plasma activation modification;
[0008] S2 is used to prepare a modified self-cleaning nano sol, which involves sequentially completing the following steps: constant temperature pretreatment of raw materials, preparation of two-component solution, controllable hydrolysis and polycondensation, functional modification of sol, light-proof constant temperature aging, precision filtration, solid content control, and sealed filling.
[0009] S3 low-pressure spray coating involves spraying nano-sol onto a ceramic substrate in stages and pre-baking it to form a uniform nano-precursor coating.
[0010] S4 gradient segmented curing, segmented heating to remove solvent and high-temperature sintering, and after cooling, a dense, transparent, self-cleaning nano-coating is formed on the ceramic surface.
[0011] S2 consists of two components: A, an organic precursor mixture, and B, an acidic catalytic hydrolysis solution. B is added to A at a uniform rate and ultrasonically dispersed to inhibit particle agglomeration. The sol is compounded with fluorosilane, nano zinc oxide, and phenyl organosilicon to achieve wear-resistant and temperature-resistant modification. After aging and filtration, the solid content of the sol is adjusted to 6-12 wt%. After spraying, gradient temperature curing is used to eliminate pinhole and bubble defects in the coating.
[0012] Preferably, the S1 ceramic substrate pretreatment step is as follows: Select the sintered ceramic substrate, and use alkaline degreasing agent and deionized water with resistivity ≥15MΩ for ultrasonic cleaning to remove oil, dust and impurities. After cleaning, dry and cool naturally to room temperature. After cooling, use low-temperature plasma to activate and modify the ceramic glaze surface to improve the micro-roughness of the substrate surface, strengthen the adhesion between the nano-coating and the ceramic substrate interface, and prevent the coating from peeling off after long-term use.
[0013] Preferably, the preparation of the S2 modified self-cleaning nanosol includes the following key control conditions: S21 Pretreatment of all basic raw materials at a constant temperature of 22℃-28℃; S22 Preparation of solution A: mixing and stirring anhydrous ethanol, tetrabutyl titanate, tetraethyl orthosilicate, and acetylacetone; Preparation of solution B: mixing anhydrous ethanol, deionized water, dilute nitric acid, and organosilicon dispersant, adjusting the pH of solution B to be stable at 1.0-1.8; S23 Adding solution B to solution A at a uniform rate of 8-15 mL / min using a peristaltic pump, refluxing at a constant temperature of 60℃-75℃ for 5-7 hours, and simultaneously ultrasonically dispersing at 120-180W; S24 Cooling to 40℃ and adding phenyl organosilicon leveling agent, nano zinc oxide precursor, and fluorosilane modification, stirring for 2-3 hours; S25 Aging in a sealed, light-protected environment at 25℃-30℃ for 18-24 hours; S26 Filtering using a 0.2μm PTFE filter element, and adjusting the sol solid content to 6-12wt% by vacuum distillation.
[0014] Preferably, the S3 substrate surface is uniformly coated using a low-pressure spraying process, with precise control of spraying pressure, spraying rate and single coating thickness. After a single spraying is completed, a short pre-baking treatment is performed, and the entire process is repeated 1-3 times to form a uniform nano-precursor coating with no thickness deviation.
[0015] Preferably, the S4 gradient segmented curing molding process consists of three heating stages: the first stage is low-temperature pre-curing, which slowly removes residual moisture and organic solvents from the coating; the second stage is medium-temperature transition heating, which eliminates minor stresses inside the coating; the third stage is high-temperature constant-temperature sintering and curing, which allows the sol components to fully cross-link and form a film; after curing, the temperature is naturally and slowly cooled to room temperature to avoid pinholes, bubbles, and cracks caused by direct high-temperature baking in one go.
[0016] Preferably, the resistivity of the deionized water used in S21 is not less than 15MΩ, so as to avoid interference from trace metal ions in the water with the hydrolysis and condensation reaction of the sol and prevent the sol from agglomerating and precipitating prematurely.
[0017] Preferably, the S23 reflux reaction is simultaneously activated with 120-180W ultrasonic dispersion treatment throughout the process. The ultrasonic cavitation effect is used to break up the native nanoparticles generated by hydrolysis, thereby avoiding the agglomeration of titanium dioxide and silicon dioxide nanoparticles from the source of the reaction and improving the storage stability of the sol.
[0018] Preferably, S24 is formulated with a synergistic blend of phenyl-modified high-temperature resistant organosilicon leveling agent, nano zinc oxide precursor, and fluorosilane modifier. Fluorosilane provides hydrophobic self-cleaning properties, phenyl organosilicon enhances the coating's high-temperature resistance, and nano zinc oxide strengthens the coating's surface abrasion and scratch resistance. The three work synergistically to extend the coating's self-cleaning service life.
[0019] Preferably, after the S26 precision filtration and solid content control are completed, the particle size distribution and room temperature storage stability of the sol are tested. Only after the test is qualified can it be sealed and filled in a light-proof, constant temperature environment to ensure that the performance of different production batches of sol is consistent and suitable for industrial continuous spraying mass production.
[0020] Compared with the prior art, the beneficial effects of the present invention are:
[0021] 1. This invention adds a low-temperature plasma activation modification process after the ceramic substrate cleaning process. Unlike traditional processes that only use water rinsing for degreasing, plasma bombardment simultaneously improves the micro-roughness of the ceramic glaze and introduces a large number of hydroxyl active groups onto the ceramic surface, enhancing the interfacial chemical bond strength between the titanium-silicon composite nano-sol and the ceramic substrate. After treatment with this improved process, the coating-substrate bond strength is enhanced. Even after long-term immersion in acidic or alkaline kitchen and bathroom wastewater and repeated wiping and friction, the coating shows no peeling, complete detachment, or localized damage, extending the lifespan of the self-cleaning ceramic coating, reducing the return rate of end products, and adapting to the long-term humid conditions of kitchens and bathrooms. This addresses the core defect of insufficient adhesion in existing products at the substrate interface level.
[0022] 2. This invention employs a dual precursor system of tetrabutyl titanate and tetraethyl orthosilicate, combined with a peristaltic pump for uniformly controlled dropwise addition of acidic catalyst and a fully ultrasonic dispersion synergistic hydrolysis process, abandoning the traditional one-time mixing hydrolysis scheme. Uniform dropwise addition allows for precise control of the hydrolysis reaction rate, avoiding excessively high local acid / alkali concentrations that could cause instantaneous agglomeration of nanoparticles; continuous cavitation dispersion using 120-180W ultrasound breaks down newly formed TiO2 and SiO2 nanoparticles in real time, inhibiting particle agglomeration. Simultaneously, a sealed, light-proof, constant-temperature aging process and a 0.2μm precision filtration process are added to remove large-particle agglomerates from the system, and the solid content is precisely controlled through vacuum distillation.
[0023] 3. In this invention, a ternary modified component compound consisting of a phenyl high-temperature resistant organosilicon leveling agent, a nano zinc oxide precursor, and a fluorosilane modifier is simultaneously added during the later stage of sol polymerization, overcoming the performance limitations of single fluorinated modified sols on the market. Fluorosilane provides the coating with low surface energy hydrophobic properties, making it difficult for water stains, oil stains, and pigments to adhere; phenyl organosilicon segments enhance the coating's high-temperature resistance, making it suitable for hot water and high-temperature steam environments in kitchens and bathrooms; nano zinc oxide is uniformly dispersed within the coating, improving the surface hardness and resistance to abrasion and scratches.
[0024] 4. This invention abandons the traditional one-time high-temperature direct baking curing method and adopts a three-stage gradient heating and curing process: low-temperature pre-solvent removal, medium-temperature stress relief, and high-temperature cross-linking sintering. This process slowly releases residual moisture and organic solvents from the coating, avoiding the formation of pinholes, bubbles, microcracks, and other defects caused by the instantaneous and violent evaporation of solvents. The cured nano-coating has a dense internal structure and a lower porosity compared to traditional processes. The entire process includes standardized procedures such as constant-temperature pretreatment of raw materials, sol aging and filtration, precise control of solid content, and full performance testing before filling. This unifies the basic performance parameters of the sol and eliminates batch differences caused by manual solution preparation and fluctuations in reaction conditions. Attached Figure Description
[0025] Figure 1 This is a process flow diagram of an improved method for preparing a self-cleaning functional ceramic surface nano-coating proposed in this invention;
[0026] Figure 2 This is a detailed flowchart of the sol preparation process in an improved method for preparing a self-cleaning functional ceramic surface nano-coating proposed in this invention.
[0027] Figure 3 This is a schematic diagram of the gradient segmented curing temperature rise curve of an improved method for preparing a self-cleaning functional ceramic surface nano-coating proposed in this invention. Detailed Implementation
[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0029] In the description of this invention, it should be understood that the terms "upper", "lower", "front", "rear", "left", "right", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0030] Reference Figure 1-3 ,
[0031] Example 1: Complete Preparation Process of Self-Cleaning Nanocoating for Ceramic Substrates in Kitchen and Bathroom Toilets
[0032] The ceramic substrate pretreatment process uses conventionally high-temperature sintered ceramic toilet blanks. The substrate glaze has been polished, with no obvious pinholes or pits. The first step involves preparing a cleaning solution using a commercially available weakly alkaline ceramic degreaser (5% concentration). The ceramic substrate is completely immersed in an ultrasonic cleaning tank at 200W for 12 minutes at room temperature to fully dissolve residual mold release agent, stamping dust, and machine oil stains from the glaze processing. After alkaline cleaning, high-purity deionized water with a resistivity of 16MΩ is used, and the ultrasonic cleaning is repeated twice, each time for 8 minutes, to thoroughly remove any residual alkaline agent from the substrate surface and prevent alkali residue from interfering with the subsequent sol-gel hydrolysis reaction. After cleaning, the ceramic substrate is placed in a hot air drying oven at 85℃ for 30 minutes. After drying, it is removed and placed in a cleanroom to cool naturally to room temperature (25℃). After cooling, the ceramic substrate was transferred to a low-temperature plasma activation device. Argon gas was used as the plasma source, with a discharge power of 300W and a vacuum chamber pressure controlled at 0.03MPa. The plasma scanned the entire outer surface of the ceramic at a speed of 12cm / min, performing two complete scans. After plasma bombardment, the micro-roughness Ra of the ceramic glaze surface increased from the original 0.12μm to 0.28μm, and the number of surface hydroxyl active groups significantly increased, completing the substrate activation and modification. The substrate was then left to stand for spraying.
[0033] The improved self-cleaning nanosol preparation process involved constant-temperature pretreatment of raw materials: The basic raw materials used in this sol preparation were 16 MΩ resistivity deionized water, analytical grade anhydrous ethanol, industrial grade tetrabutyl titanate, and industrial grade tetraethyl orthosilicate. All raw materials were transferred to a constant-temperature raw material chamber, where the temperature was stably controlled at 25℃ and allowed to stand for 4 hours to ensure uniform temperature across the entire system and eliminate fluctuations in the hydrolysis reaction rate caused by temperature differences. The two-component solutions were prepared independently: Solution A (organic precursor mixture) consisted of 420 mL anhydrous ethanol, 110 mL tetrabutyl titanate, 75 mL tetraethyl orthosilicate, and 22 mL acetylacetone. All raw materials were added to a sealed reactor equipped with a mechanical stirrer at 300 rpm for 40 minutes at room temperature until the system was completely transparent and free of stratification. The system was then sealed and allowed to stand until ready for use. Solution B (acidic catalytic hydrolysis solution) preparation ratio: 260mL anhydrous ethanol, 95mL high-purity deionized water, 7.2mL 65% dilute nitric acid, and 3.5mL organosilicon dispersant. Add these to a small stirred tank and stir at 200 rpm for 15 minutes. Monitor the pH in real time using a precision pH meter, adding a small amount of dilute nitric acid to stabilize the pH of solution B to 1.4. Seal and store for later use. S23 Controlled hydrolysis-condensation reaction: Place the reactor containing solution A in a constant-temperature oil bath. Maintain a mechanical stirring speed of 350 rpm. Turn on the peristaltic pump connected to the solution B storage tank and set the peristaltic pump dripping rate to 11mL / min. Add solution B dropwise into solution A at a uniform rate. The entire dripping process takes approximately 40 minutes. Simultaneously activate the built-in ultrasonic dispersion module at the bottom of the reactor during the dripping process, with the ultrasonic power continuously operating at 150W. After all the additions were completed, the oil bath temperature was increased to 68℃, and the reaction was carried out under constant reflux for 6 hours. The stirring and ultrasonic equipment were run continuously throughout the process, and the in-situ co-hydrolysis and condensation reaction of the titanium-silicon precursor occurred. Ultrasonic cavitation continuously dispersed the newly formed nanoparticles, and no agglomeration or clumping was formed. S24 sol functional modification and optimization: After the reflux reaction was completed, the oil bath heating was turned off, and the temperature was allowed to drop naturally to 40℃. 9 mL of phenyl-modified high-temperature resistant organosilicon leveling agent, 32 mL of 10% solid content nano zinc oxide precursor liquid, and 13 mL of fluorosilane modifier were added to the reactor in sequence. The stirring speed was maintained at 300 r / min, and the temperature was kept constant at 40℃ for 2.5 hours. The ternary modified components were fully dispersed and crosslinked into the titanium-silicon sol system, completing the hydrophobic, wear-resistant, and high-temperature resistant modification. S25 Sealed, Light-Proof, and Temperature-Controlled Aging: The modified composite sol is transferred to a black, light-proof, sealed PTFE storage tank. The tank is placed in a temperature-controlled aging chamber at a stable 27°C. The sol is completely sealed and kept in the dark for 21 hours. During this process, the short-chain oligomers within the sol undergo continuous deep condensation, resulting in uniform growth of the sol molecular chains and a significant improvement in storage stability. S26 Precision Filtration and Solid Content Control: After aging, the storage tank is transferred to a cleanroom at room temperature. The sol is allowed to cool naturally to 25°C and then pressurized using a 0.2μm pore size PTFE precision pleated filter at a pressure of 0.15MPa. This removes trace amounts of agglomerated large particles from the system, resulting in a completely clear and transparent sol after filtration.After filtration, the sol is transferred to a vacuum distillation apparatus at a vacuum level of -0.08 MPa and a distillation temperature of 45°C to slowly remove excess ethanol solvent from the system. Solid content is measured in real-time, and the sol solid content is ultimately adjusted to 9 wt% before the distillation apparatus is shut down. S27 Constant Temperature Sealing and Filling: The particle size distribution and room temperature storage stability of the sol are measured. After passing the tests, the sol is dispensed into black, light-proof plastic sealed containers. The filling environment is kept at a constant temperature of 25°C, and a small amount of nitrogen is introduced into the sealed containers to isolate air, completing the preparation of the finished sol, which can be directly used for low-pressure spraying operations.
[0034] In the uniform low-pressure spray coating process (corresponding to S3), the plasma-activated ceramic toilet substrate is fixed in an automated rotary spraying fixture. The fixture rotates at a uniform speed of 15 r / min. A low-pressure air spray gun is used, with a stable spraying pressure of 0.22 MPa. The vertical distance between the spray gun and the ceramic surface is 18 cm, and the spray gun travel speed is 30 cm / s. The first layer of nano-sol precursor coating is sprayed in a uniform reciprocating scanning motion. After a single spraying is completed, the ceramic substrate is sent to an 80℃ pre-baking oven for 10 min to remove free solvent from the coating surface. After pre-baking, the substrate is removed, and the second layer of sol is sprayed again, followed by a short pre-baking. In this embodiment, a total of 2 layers are sprayed. After the two sprayings are superimposed, the thickness of the nano-precursor coating on the ceramic surface is uniform, without defects such as missed spraying, dripping, or uneven thickness.
[0035] The gradient segmented curing process (corresponding to S4) involves pushing the pre-baked ceramic substrate with double-layer spraying into a segmented hot air curing oven. The oven is set with three gradient heating programs, with the heating rate strictly controlled at 2℃ / min throughout: The first stage is a low-temperature pre-curing zone, where the temperature is uniformly increased from room temperature to 130℃ and held at a constant temperature for 45 minutes to slowly remove residual moisture and low-boiling-point ethanol solvent from the coating, preventing rapid solvent evaporation and the formation of pinholes and bubbles; the second stage is a medium-temperature transition zone, where the temperature is uniformly increased from 130℃ to 260℃ and held at a constant temperature for 30 minutes to eliminate internal stress caused by the temperature difference between the inside and outside of the coating, preventing the coating from cracking during the high-temperature sintering stage; the third stage is a high-temperature sintering and curing zone, where the temperature is uniformly increased from 260℃ to 420℃ and held at a constant temperature for 60 minutes, allowing the titanium silicate sol component to fully cross-link into a dense inorganic composite film, and the fluorosilane, organosilicon, and zinc oxide components to be uniformly cured and embedded into the coating skeleton. After all three curing stages are completed, turn off the oven heating system and keep the oven door slightly open for slow, natural cooling. The entire cooling process takes 120 minutes. Once the substrate has cooled to room temperature, remove it from the oven. A completely transparent, non-visible nano-self-cleaning coating will be formed on the ceramic surface.
[0036] Example 2: The overall process flow for preparing anti-slip ceramic floor tile substrate is completely consistent with Example 1, with only some process parameters adjusted to adapt to mass production of floor tiles: the plasma scanning speed for ceramic floor tile pretreatment is adjusted to 15 cm / min; the constant temperature pretreatment temperature in the sol preparation stage is 23℃, the droplet acceleration of liquid B is 9 mL / min, the reflux reaction temperature is 63℃, the reflux time is 5.5 h, the aging temperature is 26℃, the aging time is 19 h, and the solid content of the sol after vacuum distillation is adjusted to 7 wt%; the spraying process involves repeated spraying of 3 layers, with each layer pre-baking for 8 min; the maximum sintering temperature for gradient curing is adjusted to 390℃, and the high-temperature holding time is 50 min. Batch-prepared floor tile samples were placed in a high-temperature and high-humidity environment in kitchens, bathrooms, and open balconies for continuous testing for 12 months. The hydrophobic angle of the glaze remained above 108°, oil stains could be completely removed by rinsing with water after spraying, with no stubborn stains remaining, and the coating showed no scratches or peeling.
[0037] Example 3: The basic process flow for preparing industrial wear-resistant special ceramic parts remains unchanged, with targeted adjustments to wear-resistant modification parameters: the amount of nano-zinc oxide precursor solution added in the sol-gel modification stage is increased to 45 mL, and the fluorosilane modifier is 10 mL; the sol solid content is controlled to 11 wt%; plasma activation scanning is repeated 3 times to improve surface roughness; only one layer is sprayed at a time, and the pre-baking time is extended to 15 min; the gradient curing high-temperature sintering temperature is increased to 450℃, and the holding time is 70 min. After preparation, the special ceramic parts undergo 5000 cycles of reciprocating friction testing with steel wool. The coating shows no wear to the substrate, and the photocatalytic self-cleaning performance decays by less than 8%, making it suitable for long-term use in industrial oily conditions.
[0038] Comparative Example: The traditional single-titanium source sol-gel process, involving one-time mixing, no plasma activation, and one-time high-temperature curing, uses the same ceramic toilet substrate. It uses only tetrabutyl titanate as the single titanium source to prepare the sol, without tetraethyl orthosilicate compounding. The substrate is simply rinsed with water without plasma activation. The catalytic hydrolysis solution is poured entirely into the precursor at once, without controlled dripping or ultrasonic dispersion. After spraying, it is directly baked at 420℃ for 90 minutes without gradient heating. After three months of use in the kitchen and bathroom, the finished samples showed localized peeling and flaking of the glaze, with the surface covered in fine pinholes. Oil stains could not be rinsed off with water. The sol stock solution showed obvious white precipitate after standing for four days. The hydrophobic angle difference between different batches of samples exceeded 20°, indicating extremely poor mass production stability. This fully demonstrates the performance improvement effect brought about by the synergistic improvement of each process in this invention.
[0039] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. An improved method for preparing a self-cleaning functional ceramic surface nano-coating, characterized in that, The improved preparation method includes the following steps: S1 ceramic substrate pretreatment, cleaning and drying, followed by low-temperature plasma activation modification; S2 is used to prepare a modified self-cleaning nano sol, which involves sequentially completing the following steps: constant temperature pretreatment of raw materials, preparation of two-component solution, controllable hydrolysis and polycondensation, functional modification of sol, light-proof constant temperature aging, precision filtration, solid content control, and sealed filling. S3 low-pressure spray coating involves spraying nano-sol onto a ceramic substrate in stages and pre-baking it to form a uniform nano-precursor coating. S4 gradient segmented curing, segmented heating to remove solvent and high-temperature sintering, and after cooling, a dense, transparent, self-cleaning nano-coating is formed on the ceramic surface. S2 consists of two components: A, an organic precursor mixture, and B, an acidic catalytic hydrolysis solution. B is added to A at a uniform rate and ultrasonically dispersed to inhibit particle agglomeration. The sol is compounded with fluorosilane, nano zinc oxide, and phenyl organosilicon to achieve wear-resistant and temperature-resistant modification. After aging and filtration, the solid content of the sol is adjusted to 6-12 wt%. After spraying, gradient temperature curing is used to eliminate pinhole and bubble defects in the coating.
2. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, The S1 ceramic substrate pretreatment steps are as follows: Select the sintered ceramic substrate, and use alkaline degreasing agent and deionized water with resistivity ≥15MΩ for ultrasonic cleaning to remove oil, dust and impurities. After cleaning, dry and cool naturally to room temperature. After cooling, use low-temperature plasma to activate and modify the ceramic glaze, improve the micro-roughness of the substrate surface, strengthen the adhesion between the nano-coating and the ceramic substrate interface, and prevent the coating from peeling off after long-term use.
3. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, The preparation of the S2 modified self-cleaning nanosol involves the following key control conditions: S21 Pretreatment of all basic raw materials at a constant temperature of 22℃-28℃; S22 Preparation of solution A: mixing and stirring anhydrous ethanol, tetrabutyl titanate, tetraethyl orthosilicate, and acetylacetone; Preparation of solution B: mixing anhydrous ethanol, deionized water, dilute nitric acid, and organosilicon dispersant, adjusting the pH of solution B to a stable 1.0-1.8; S23 Adding solution B to solution A at a uniform rate of 8-15 mL / min using a peristaltic pump, refluxing at a constant temperature of 60℃-75℃ for 5-7 hours, and simultaneously ultrasonically dispersing at 120-180W; S24 Cooling to 40℃ and adding phenyl organosilicon leveling agent, nano zinc oxide precursor, and fluorosilane modification, stirring for 2-3 hours; S25 Aging in a sealed, light-protected environment at 25℃-30℃ for 18-24 hours; S26 Filtering using a 0.2μm PTFE filter element, and adjusting the sol solid content to 6-12wt% by vacuum distillation.
4. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, The S3 substrate surface is uniformly coated using a low-pressure spraying process, which precisely controls the spraying pressure, spraying rate, and single coating thickness. After each spraying, a short pre-baking treatment is performed. The entire process is repeated 1-3 times to form a uniform nano-precursor coating with no thickness deviation.
5. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, S4 gradient segmented curing molding consists of three heating stages: the first stage is low-temperature pre-curing, which slowly removes residual moisture and organic solvents from the coating; the second stage is medium-temperature transition heating, which eliminates minor stresses inside the coating; and the third stage is high-temperature constant-temperature sintering curing, which allows the sol components to fully cross-link and form a film. After curing, the product is allowed to cool naturally and slowly to room temperature, avoiding pinholes, bubbles, and cracks caused by direct high-temperature baking in one go.
6. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, The resistivity of the deionized water used in S21 is not less than 15MΩ, so as to avoid interference from trace metal ions in the water with the hydrolysis and condensation reaction of the sol and prevent the sol from agglomerating and precipitating prematurely.
7. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, The S23 reflux reaction is simultaneously activated with 120-180W ultrasonic dispersion treatment throughout the process. The ultrasonic cavitation effect is used to break down the native nanoparticles generated by hydrolysis, avoiding the agglomeration of titanium dioxide and silicon dioxide nanoparticles from the source of the reaction and improving the storage stability of the sol.
8. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, S24 is formulated with a synergistic blend of phenyl-modified high-temperature resistant silicone leveling agent, nano zinc oxide precursor, and fluorosilane modifier. Fluorosilane provides hydrophobic self-cleaning properties, phenyl silicone enhances the coating's high-temperature resistance, and nano zinc oxide strengthens the coating's surface abrasion and scratch resistance. The three work together to extend the coating's self-cleaning service life.
9. The improved method for preparing a self-cleaning functional ceramic surface nano-coating according to claim 1, characterized in that, After S26 precision filtration and solid content control are completed, particle size distribution and room temperature storage stability tests are conducted on the sol. Only after passing the tests can it be sealed and filled in a light-proof, constant-temperature environment to ensure that the performance of different production batches of sol is consistent and suitable for industrial continuous spraying mass production.